Affirmative action and educational attainment of disadvantaged religious minorities: Evidence from India. - Surana, Mitul; Rai, Rajnish (Economic Inquiry, 2025)
We examine whether affirmative action incentivizes a disadvantaged religious minority group in India to obtain additional years of education. We study the implementation of quotas in government hiring and university admissions for backward‐class Muslims in 2007 in the Indian state of Andhra Pradesh. Using a difference‐in‐differences approach that uses variation in exposure to the policy by age‐cohort and social group, we find that these quotas increase educational attainment of the targeted population. Investigating the effects by gender, we find statistically significant and robust positive effects on the educational attainment of male members of the targeted Muslim groups, but not females.